Assessing the impact of biodiversity on tourism flows: A model for tourist behaviour and its policy implications - Giulia Macagno; Maria Loureiro; Paulo A. L.D. Nunes; Richard Tol (The Economic and Social Research Institute (ESRI), 2009)
This analysis provides an example of how biodiversity can be measured by means of different indicators, and how the latter can be used to assess the influence of the biodiversity profile of a region on the tourism flows towards it. Previous studies have considered environmental amenities as one of the determinants of tourism destination choice. The central hypothesis of this paper is that the destination's biodiversity profile can be considered as a key component of environmental amenities. The main objective of this study is to propose a different perspective on this topic, considering the role of biodiversity on tourists? choice of destination and duration of stay. Domestic Irish tourist flows have been chosen as a case study. The first step of the analysis required the construction of biodiversity indicators suitable for developing a biodiversity profile of each Irish county. Subsequently, a model was developed so as to explain the total number of nights spent in any location as a function of a set of explanatory variables including information about the sociodemographic characteristics of respondents, biodiversity and the landscape profile of the county of destination and features of the trip. Results show that most of the biodiversity and landscape indicators included in the analysis turn out to be statistically significant in determining tourists? choices regarding the duration of their trip. As a result, policies pursuing biodiversity conservation appear to have a positive impact on the revenue of regional tourism.
Keywords: Q57; 330; species diversity; habitat fragmentation; landscape diversity; trip demand; indicators; ecosystem services; human well-being; Biodiversität; Umweltökonomik; Urlaubsverhalten; Naturschutz; Irland